Cardioprotective effect of histamine H2 antagonists in congestive heart failure: A systematic review and meta-analysis. Issue 15 (April 2018) - Zhang, Juan; Cai, Wen-Ke; Zhang, Zheng; Wang, Ping; Lin, Xiao-Qian; Feng, Ju; Fu, Suo-Chao; He, Gong-Hao
Abstract: Background: Histamine H2 antagonists (H2RAs) have long been suggested to have beneficial effects on congestive heart failure (CHF). However, full agreement about the cardioprotective effects of H2RAs is still not reached yet. Therefore, this study aims to clarify the effects of H2RAs on myocardial function in CHF patients by meta-analysis. Methods: Electronic databases including PubMed, Embase, and Cochrane Library were retrieved. Randomized controlled trials comparing the cardiac effects of H2RAs and placebo or other medicines were collected. Pooled mean differences (MDs) with 95% confidence intervals (CIs) were calculated and meta-analysis was performed using RevMan 5.3 software. Results: A total of 10 studies (472 participants) were included in this meta-analysis. H2RAs exhibited significant negative inotropic and chronotropic effects to reduce heart rate (MD: –3.90; 95%CI: –7.07 to –0.73, P  = .02). Furthermore, although H2RAs did not affect the blood pressure in health volunteers, they significantly decreased the blood pressure of CHF patients. Additionally, H2RAs were also associated with significant increase in pre-ejection period and the ratio of pre-ejection period to left ventricular ejection time. Conclusion: In summary, these findings showed that H2RAs exerted negative inotropic and chronotropic effects to reduce heart rate and blood pressure, which, similar to beta-adrenergic receptor blockers, might decrease myocardial oxygen demand and eventually result in improvement of CHF symptoms. These data provided further evidence for the effect of H2RAs on cardiac function and novel potential strategy for treatment of CHF. Abstract : Supplemental Digital Content is available in the text